Outcome of Therapeutic Penetrating Keratoplasty Using Glycerol-Preserved Donor Corneas in Infectious Keratitis. Issue 9 (September 2016) - Thanathanee, Onsiri; Sripawadkul, Wathanee; Anutarapongpan, Orapin; Luanratanakorn, Patanaree; Suwan-Apichon, Olan
Abstract : Purpose: To report the surgical outcomes and complications of therapeutic penetrating keratoplasty (TPK) using glycerol-preserved corneas in infectious keratitis. Methods: This is a retrospective, noncomparative case series of patients with severe infectious keratitis who received TPK using glycerol-preserved corneas from 2004 to 2014 in the Department of Ophthalmology, Srinagarind Hospital, Khon Kaen University. The medical records were reviewed for baseline characteristics, visual outcomes, recurrence rate, wound integrity, secondary glaucoma, and donor cornea storage times. Results: Twenty-two eyes from 22 patients were included. Age ranged from 28 to 85 years and the donor cornea sizes ranged from 7.5 to 9.5 mm. The most common causative agents were fungi (16/22, 72.7%). Eleven patients (50.0%) developed secondary glaucoma and 7 patients (31.8%) had wound leakage. Recurrence of infection was observed in 15 patients (68.2%) and 9 patients (40.9%) received enucleation or evisceration. Thirteen globes (59.1%) were saved and the final visual acuites ranged from 1/60 to light perception. The storage times of donor corneas varied between 2 days and 62 months. The length of donor cornea storage did not affect the success rate of surgical outcome. Conclusions: TPK using glycerol-preserved corneas has a high rate of secondary glaucoma and recurrence of infection with unsatisfactory visual results. These corneas may be used as temporary emergency transplants in infectious keratitis when fresh corneas are unavailable to meet demands.